2015
DOI: 10.1093/ntr/ntv238
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Stress Symptoms and Their Association With Smoking Outcome Expectancies Among Homeless Smokers in Boston

Abstract: Introduction: Cigarette smoking and traumatic life experiences are each common among homeless adults, but the prevalence and correlates of posttraumatic stress disorder (PTSD) symptoms among homeless smokers are not known. We assessed symptoms of PTSD and their association with smoking outcome expectancies in a sample of homeless smokers in Boston. Methods: We used time-location sampling to conduct an in-person survey of homeless adult smokers using Boston Health Care for the Homeless Program clinical services… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 51 publications
0
17
0
Order By: Relevance
“…Of these studies, nine studies found significant associations between PTSD diagnosis and nicotine dependence. In particular, six found higher levels of nicotine dependence among individuals with PTSD compared to those without PTSD (Mitchell, Van Voorhees, Dennis, et al, 2012;Vrana et al, 2013;Vrana, Calhoun, Dennis, Kirby, & Beckham, 2015) or any other psychiatric condition (Baggett et al, 2016;Beckham, Calhoun, Dennis, Wilson, & Dedert, 2013;Wilson, Dedert, Dennis, et al, 2014), and three found that diagnosis of PTSD was associated with increased risk for nicotine dependence (Cougle et al, 2010;Greenberg et al, 2012;Roberts, Chikovani, Makhashvili, Patel, & McKee, 2013). It should be noted that the proportion of individuals with other psychiatric conditions in these studies was extremely low (≤6%).…”
Section: Nicotine Dependencementioning
confidence: 63%
See 3 more Smart Citations
“…Of these studies, nine studies found significant associations between PTSD diagnosis and nicotine dependence. In particular, six found higher levels of nicotine dependence among individuals with PTSD compared to those without PTSD (Mitchell, Van Voorhees, Dennis, et al, 2012;Vrana et al, 2013;Vrana, Calhoun, Dennis, Kirby, & Beckham, 2015) or any other psychiatric condition (Baggett et al, 2016;Beckham, Calhoun, Dennis, Wilson, & Dedert, 2013;Wilson, Dedert, Dennis, et al, 2014), and three found that diagnosis of PTSD was associated with increased risk for nicotine dependence (Cougle et al, 2010;Greenberg et al, 2012;Roberts, Chikovani, Makhashvili, Patel, & McKee, 2013). It should be noted that the proportion of individuals with other psychiatric conditions in these studies was extremely low (≤6%).…”
Section: Nicotine Dependencementioning
confidence: 63%
“…The lowest rate of PTSD among current users of tobacco products was found in a study involving cigarette smokers from the general population (3.0%) (Zvolensky et al, 2014) whereas the highest rate of PTSD among current users of tobacco products was reported in a study of homeless cigarette smokers (66.3%) (Baggett et al, 2016). Results are graphically displayed in Other studies explored rates of current or history of PTSD among current or former users of tobacco products.…”
Section: Prevalence Of Ptsd Among Individuals Using Tobacco Products mentioning
confidence: 98%
See 2 more Smart Citations
“…From April to July 2014, we used time-location sampling [ 21 – 24 ] to conduct an in-person survey of homeless adult smokers at 5 high-volume BHCHP clinical sites. Our sampling design and survey procedures are described in-depth elsewhere [ 25 , 26 ]. Participants were required to be proficient in English, ≥18 years old, current cigarette smokers, and currently homeless.…”
Section: Methodsmentioning
confidence: 99%